Effect of Antiretroviral Drug (arved) on the Kidney in Albino Rat - D E Peters; A A Uwakwe; C C Monago (Journal of Applied Sciences and Environmental Management, 2014)
African studies on effect of antiretroviral drugs on the kidney are limited resulting to scanty information on the safety of these drugs. This study was therefore designed to evaluate the effects of antiretroviral drugs arved®, on creatinine, urea, potassium and sodium ions as well as histological effect on the kidney. A total of fifty two (52) albino rats were randomly divided into four groups labeled A, B, C and D and kept in a well ventilated room. All experimental groups shared the same environmental conditions. Group A served as the control and rats were treated with distil water. Rats in groups B, C and D were, respectively treated with three different doses of arved (1.07, 3.21, and 4.29 mg kg-1). The drug was administered orally daily for 2, 4, 6, and 8 consecutive weeks. Animals were sacrificed twenty four hours after the last treatment. Blood samples were collected into heparinized sample bottles for biochemical analyses. The result of this study revealed a significant decrease (p<0.05) in blood urea level in weeks 4 and 6 for treatment groups B and C when compared to control group. Mean creatinine values for all the treatment groups significantly increased (p<0.05) over the period of treatment when compared to the control value. Sodium ion showed a non significant increase (p>0.05) all through the period of treatment. Significant increase (of about 2 fold) (p<0.05) of potassium ion was observed in all the treatment groups in weeks 6 and 8 of treatment. Histological examination of the kidney tissue of rats in group D treated with the drug for 8 weeks did not show any morphological change similar to that of the control group. In conclusion prolonged treatment of HIV/AIDS patients with arved could result to renal dysfunction.